(3CKQ HQfGeL bGFe Ydi JhXja eG hQGA GdeYQaI aj CSdhH GdMd GdEHJcGQj ddeTcdGJ GdQjGVjI dOi GdJdGejP GdYGOjjf hPhj UYhHGJ GdJYde aj GdeQMdI GdEYOGOjI (B: s (3OQGSI JLQjHjI ebGQfI (B/ s - (3SYGO SjO fUQ QaGYjs; (3QTG SejQ YhV (B: s; (3eMeO YGWa YWjaj (B: s ((3GdbGgQI (B: s (3SYGO SjO fUQ QaGYj (B: s, 2015)
(3JgOa GdOQGSI GdMGdjI Edi GdJYQa Ydi CKQ HQfGeL bGFe Ydi JhXja eG hQGA GdeYQaI aj CSdhH GdMd GdEHJcGQj ddeTcdGJ GdQjGVjI dOi GdJdGejP GdYGOjjf hPhj UYhHGJ GdJYde aj GdeQMdI GdEYOGOjI(B: (3Ydi YjfI (B( 110 (3JdejP hJdejPI (B) (3ef JdGejP GdUa GdKGfj GdEYOGOj GdYGOjjf hPhj UYhHGJ GdJYde aj GdQjGVjGJ(B: (3Je JOQjHge Ydi GSJQGJjLjGJ hegGQGJ eG hQGA GdeYQaI dJMSjf GdMd GdGjJcGQj ddeTcdGJ GdQjGVjI dOjge (B: (3hJe GdhUhd deYGOdI JfHDjI deSJhi GdMd GdEHJcGQj ddeTcdGJ GdQjGVjI ef NdGd egGQGJ eG hQGA GdeYQaI dOi GdJdGejP GdYGOjjf hPhj UYhHGJ GdJYde aj GdQjGVjGJs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3eYgO GdOQGSGJ hGdHMhK GdJQHhjI (B- (3bSe Yde GdfaS GdJQHhis
(3UOQ GjVG cbQU eOeLs
Keywords: (3CKQ HQfGeL bGFe Ydi JhXja eGhQGAGdeYQaI s; (3GdJdGejP GdYGOjjf hPhj UYhHGJ JYde GdQjGVjGJ s; (3GdMd GdEHJcGQi ddeTcdGJ GdQjGVjI s